2007
DOI: 10.1177/0047287507304049
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Cognitive and Affective Image in Predicting Choice Across Natural, Developed, and Theme-Park Destinations

Abstract: This study examines the role of cognitive and affective destination-image components in the formation of destination preferences from a multialternative/multiattribute perspective. In addition, the study examines the stability of those roles across three types of destinations. A total of 1,020 Taichung residents in Taiwan were administered an on-site questionnaire. The results indicated that cognitive and affective components of overall destination image influence tourists' destination preferences and that cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
178
4
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(212 citation statements)
references
References 44 publications
18
178
4
12
Order By: Relevance
“…In the space syntax model, intelligence value can measure whether the local space and the whole space are related and unified [9]. Generally, the range of the intelligence value R 2 is 0-0.5, which indicates that the spatial identifiability is weak; R 2 locates at 0.5-0.7 which indicates that the spatial identifiability is good; R 2 locates at 0.7-1.0 which indicates that the space recognizability is strong [32].…”
Section: Interpreting the Spatial Syntax Analysis Of Nanyangmentioning
confidence: 99%
“…In the space syntax model, intelligence value can measure whether the local space and the whole space are related and unified [9]. Generally, the range of the intelligence value R 2 is 0-0.5, which indicates that the spatial identifiability is weak; R 2 locates at 0.5-0.7 which indicates that the spatial identifiability is good; R 2 locates at 0.7-1.0 which indicates that the space recognizability is strong [32].…”
Section: Interpreting the Spatial Syntax Analysis Of Nanyangmentioning
confidence: 99%
“…Th e emotional or aff ective component of the image refers to feelings about the place (Baloglu & Brinberg, 1997;Beerli & Martin, 2004b;Kim & Richardson, 2003;Martin & Rodríguez del Bosque, 2008;Russell & Pratt, 1980). Th e cognitive component is considered an antecedent of the aff ective component, given that evaluation draws on the knowledge that individuals have about the objects (Agapito, Valle, & Mendes, 2013;Baloglu & Brinberg, 1997;Beerli & Martín, 2004a, 2004bBeerli-Palacio & Nazzareno, 2017;Gartner, 1993;Lin, Morais, Kerstetter, & Hou, 2007;Nghiêm-Phú, 2014;Qu et al, 2011;Russell, Ward, & Pratt, 1981;Stern & Krakover, 1993;Stylidus et al, 2017).…”
Section: Components Of Destination Imagementioning
confidence: 99%
“…The cognitive component refers to the beliefs and the knowledge held by tourists regarding a destination's attributes [45] and the affective component is defined by their feelings or emotional responses [46]. From a theoretical point of view, there is a general agreement that the cognitive component is an antecedent of the affective component [47][48][49][50][51]. For instance, Lin et al [48] demonstrated that tourists develop feelings about a destination only after they cognitively evaluate it.…”
Section: The Impacts Of Dsr On Destination Image and Tourist Loyaltymentioning
confidence: 99%
“…From a theoretical point of view, there is a general agreement that the cognitive component is an antecedent of the affective component [47][48][49][50][51]. For instance, Lin et al [48] demonstrated that tourists develop feelings about a destination only after they cognitively evaluate it. Based on the discussions above, we can formulate the following hypotheses:…”
Section: The Impacts Of Dsr On Destination Image and Tourist Loyaltymentioning
confidence: 99%